Sorption of lead on modified silica obtained from chrysotile: isotherms application - Silva Filho, Edson Cavalcanti da; Fortes, Antônio Wuiston Martins; Reis, Luizângela da Silva; Santos, Maria Rita de Morais Chaves; Santos Júnior, Luiz de Sousa; Fonseca, Maria Gardênnia da (Comunicata Scientiae, 2010)
A silica was modified with three alcoxysilanes with different quantities of nitrogen, whose the silica obtained from chrysotile acid leaching. The modified silicas were applied in lead removal from aqueous solution, obtained the following capacities: 1.41, 0.78 e 0.60 mmol g-1 for the materials containing 3, 1 and 2 nitrogen in organic chains, respectively. The isotherms were adjusted using different models, and each material showed affinity to a model. The interactions were favorable and spontaneous from Freundlich model and Gibbs free energy, respectively.